Review of the population structure and ecology of S. mentella in the Irminger sea and adjacent waters - Saborido-Rey, Fran; Garabana, Dolores; Stransky, Christoph; Melnikov, Sergey; Shibanov, Vladimir (Reviews in Fish Biology and Fisheries, 2004)
25 páginas, 11 figuras Significant controversies exist over the three types of Sebastes mentella found in the Irminger Sea and adjacent waters. Preliminary genetic studies have given evidence for the existence of three distinct groups, characterized using several molecular genetic markers. The biological or ecological significance of these between-group differences has, however, not been evaluated. In the present paper, we review the life cycle of S. mentella in this area, based on published data. Spawning of S. mentella in the Irminger Sea takes place in a single area above Reykjanes Ridge. The larvae drift towards East Greenland from where they are carried to West Greenland (NAFO Subareas 0+1). Later they return to East Greenland where the main nursery area has been identified. There is evidence for a migration of juvenile fish from the nursery area into the open Irminger Sea, where many different cohorts spawn. We also compare these ecological data with the genetic results and we conclude that the observed genetic differences can be derived from possible genetic drift, selection or mostly from temporal variation (age dependency) which has also been reported for other species with as high longevity as S. mentella. We conclude that S. mentella in the Irminger Sea and adjacent waters comprises one single population. The present study was realized both within Russian national research programmes and the REDFISH project (QLK5-CT1999-01222), financially supported by the European Commission within the research framework QUALITY OF LIFE AND MANAGEMENT OF LIVING RESOURCES, Key Action 5: Sustainable Agriculture, Fisheries and Forestry. Peer reviewed